LINGUISTIC IDENTITY AND CULTURAL SELFHOOD IN THE CONTEXT OF GLOBALIZATION - Kalandarova Ruhshona Bunyodovna (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article explores the intricate relationship between globalization and linguistic identity, emphasizing how global integration affects individual and collective cultural selfhood. It examines the tension between dominant global languages and local linguistic identities, highlighting the role of education, policy, and community practices in safeguarding cultural and linguistic heritage. Special attention is given to identity formation, multilingual education, and strategies to maintain cultural and linguistic self-awareness in a globalized environment.